The Silence, Exile, and Cunning of “I”: An Analysis of Bildungsroman as the Place Model in the Work of Charlotte Brontë and James Joyce - Kathryn White; Frank Ferguson (Education Sciences, 2019)
Education, be that on a moral, social or intellectual level, in a formal setting or via lived experience is Bildungsroman’s raison d’être. ‘Moments of crisis’ and the resultant demonstration of the journey towards awareness of personal autonomy, agency, identity and place are discussed via geographical imagination. This article examines ‘fictional’ teachers, the impact of the ‘professional’ on formative development and how the fictional characters of Jane Eyre and Stephen Dedalus fit within and extend the Place Model.